(untitled) (Bangladesh Journal of Botany, 2019)
An efficient in vitro regeneration system was developed for Piper betle L. through direct and indirect organogenesis from nodal segment, leaf segment and petiole explants. Highest direct regeneration was recorded when nodal explants were cultured on MS with 1.0 mg/l BAP and 1.0 mg/l Kn where 80% explants produced multiple shoots and the average number of shoots per explants were 3.20. Remarkable results on callus induction and shoot initiation were observed when the explants cultured on MS + 2.0 mg/l BAP + 0.5 mg/l Kn + 1.0 mg/l IAA. It was observed that nodal explants were showed best response on shoot/explants 13.2 ± 4.5 after 8 weeks of callus culture on MS medium with 0.5 mg/l BAP. The best response towards root induction was observed on half strength of MS with 0.25 mg/l IBA. The well rooted plants were successfully acclimatized and transferred to soil.